2013
DOI: 10.4085/1062-6050-48.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Pain and Effusion and Quadriceps Activation and Strength

Abstract: Context: Quadriceps dysfunction is a common consequence of knee joint injury and disease, yet its causes remain elusive.Objective: To determine the effects of pain on quadriceps strength and activation and to learn if simultaneous pain and knee joint effusion affect the magnitude of quadriceps dysfunction.Design: Crossover study. Setting: University research laboratory.Patients or Other Participants: Fourteen (8 men, 6 women; age ¼ 23.6 6 4.8 years, height ¼ 170.3 6 9.16 cm, mass ¼ 72.9 6 11.84 kg) healthy vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
68
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 29 publications
5
68
0
4
Order By: Relevance
“…In the present study, the observed knee swelling-quadriceps strength association persisted in multivariable models adjusted for knee pain intensity, and these findings seem to corroborate those from previous experimental studies which have demonstrated a link between relatively pain-free knee swelling and reduced voluntary quadriceps activation [5][6][7][8][9][10]. In the context of patients with TKA, independent of knee pain [26], voluntary muscle activation was found to be a determinant of quadriceps strength [26,27].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the observed knee swelling-quadriceps strength association persisted in multivariable models adjusted for knee pain intensity, and these findings seem to corroborate those from previous experimental studies which have demonstrated a link between relatively pain-free knee swelling and reduced voluntary quadriceps activation [5][6][7][8][9][10]. In the context of patients with TKA, independent of knee pain [26], voluntary muscle activation was found to be a determinant of quadriceps strength [26,27].…”
Section: Discussionsupporting
confidence: 93%
“…Because quadriceps weakness is a major contributor to gait speed limitations in TKA [2,4] and because experimental studies in healthy volunteers have demonstrated a putative link between knee swelling and quadriceps strength [5][6][7][8][9][10], understanding the associations between knee swelling, quadriceps strength, and gait limitations in TKA is crucial. Thus, the present study uniquely used bioimpedance spectrometry to quantify knee swelling in patients with TKA and it aimed to (i) describe the time course of knee swelling over a 3-month post-TKA period and (ii) examine the longitudinal associations of knee swelling with quadriceps strength and gait speed.…”
mentioning
confidence: 99%
“…1,2 The contralateral knee may be at greater risk of injury than the involved knee, 2 suggesting possible postinjury bilateral neurologic alterations or the presence of bilateral factors that contributed to the initial injury. 3 Researchers have reported that these postinjury neurologic differences include disrupted central nervous system afferent function, 4,5 altered efferent output, 3,6 and changes in brain activity for motor control. 7,8 Few investigators have prospectively studied the neurologic changes that occur in the brain after ACL injury, reconstruction, and rehabilitation and before subsequent injury.…”
mentioning
confidence: 99%
“…13 Therefore, given the inflammatory status of the patient being treated, clinicians may elect to use 1 of the disinhibitory modalities over the other. Patients with chronic knee pathologies who demonstrate quadriceps activation failure should be instructed to use TENS more than cryotherapy, unless they are attempting to control the onset of swelling and inflammation after exercise or activity.…”
Section: Implications For Practice Education and Future Researchmentioning
confidence: 99%